Factors Influencing the Fish Consumption Preferences: Understandings from the tribes of Wayanad, Kerala - Sajeev, M. V.; Radhakrishnan, Aparna; Mohanty, A. K.; Joshy, C. G.; Ali, V. P. Akber; Gopika, R.; Mathew, Suseela; Ravishankar, C. N. (Indian Journal of Extension Education, 2021)
Fish consumption preferences vary with communities. The study aims to study the socio-personal and fish consumption profile of the seven major tribes of Wayanad, Kerala. Species preferences, factors affecting the fish purchase and consumption, health profile and symptoms of tribes in relation with iron deficiency anaemia, association between fish consumption and health of tribes were investigated. Data were gathered through a questionnaire completed by 200 tribal households from different socioeconomic backgrounds. Results indicate that Sardine was the most consumed and preferred fish and percapita fish consumption of tribes was far below the state average. In conclusion, the price of fish ranked as the first and foremost important factor affecting the fish purchase and consumption of the tribes surveyed, and the fish consumption variables were highly associated with health values. Increasing awareness about the health benefits of fish consumption and building capacity of tribes to prepare fish-based products based on their taste and preferences can aid improved fish consumption among Wayanad tribes. Therefore, to establish and adopt fish consumption guidelines for the tribes of Wayanad, the factors mentioned in the study need to be integrated into the projects and policies.
Keywords: Factors; Fish consumption; Kerala; Tribes; Wayanad